THE DEVELOPMENT OF FIN SWIMMING INSTRUCTION PACKAGE FOR NAVAL CADETS ACADEMY - Taufik Shigit Noveriyanto; Nurmida Catherine Sitompul; Yoso Wiyarno (JOURNAL ASRO, 2020)
Instruction package is a learning instruction containing teaching material directed at the achievement of instructional objectives to be given to educators and students, which includes lesson plans, lesson programs, educational and training books, student exercise books, testing tools and a list of instructional tools. In military education lecturers or educators must be able to provide and present material well and it is hoped that cadets can apply it when practical training is carried out. Therefore PI is very necessary for the success of a practice exercise. Cadets is a soldier of the Naval Academy students as individuals who are guided, cared for, assisted and trained until they become officers. Fin swimming is a water sport activity that is carried out by a swimmer by using a mask, snorkel and fins equipment, to be able to dive, move faster in water and last longer on the surface of the water. In this research, the formulation of the problem examined is what factors need to be developed to improve the quality of PI Fin Swimming in order to help facilitate the understanding of Naval Cadets Academy with sub-problems are the feasibility of the content, linguistic aspects, presentation aspects and graphic aspects. The research instrument used in the questionnaire was closed and open questions. Data analysis is carried out through the process of triangulating data and information obtained when conducting research or direct observation. The respondents were cadets of Level IV Naval Academy, Teaching Materials Expert, Head of the Physical Department. The selection of respondents is done by purposive random sampling technique. The factors that must be corrected from each item aspects are as follows: aspects of the appropriateness of contents or material that are generally included in the good category, sub-aspects that get enough votes from respondents are conformity with the development of science and technology and examples are quite varied and applicable but not yet can motivate more cadets to find more appropriate movement techniques during learning, linguistic aspects are generally included in the good category, sub-aspects that get sufficient assessment from respondents are the clarity of information conveyed and are quite interactive so that cadets still have difficulty understanding even more so when studied by themselves, aspects of the presentation in general are included in either category, sub-aspects that get less assessment from the respondent is the column of learning material summary, aspects of graphics in general. The results of the evaluation were followed up by developing a PI and respondents were asked to provide a response. The responses of each respondent can be concluded in general that the PI Fin Swimming results of the development were good and fulfilled every aspect of the PI as a teachingmaterial for Cadets.Keywords: Instruction Package, Cadets, Development, Fin Swimming